The Implementation of Teaching and Learning Process of Islamic Study in Universities in Indonesia - Anwar, Fuady; Rahman, Rini; Zein, Zainurni (Khalifa Journal of Islamic Education, 2017)
The goal of national education is to develop the students’ potential to become virtuous, courteous, healthy, knowledgeable, skillful, creative, independent, democratic and responsible human beings, and be devoted to Allah S.W.T. In its implementation, Islamic Study subject has an important and strategic role in realizing the goals of national education. Generally, the teaching and learning process of this subject in university level is much better compared to the previous one, in either lecturer’s competence, curriculum or management system. Nevertheless, the fact also shows that most students take this subject only to complete the requirement of their study, not as a scientific need. This course has been designed to build the students’ charcaters and personality so that they could become knowledgeable and devoted to Allah SWT. Therefore, strategic steps based on more open and advanced paradigm and thought are needed. This article is intended to discuss strategic steps required in managing and conducting the teaching and learning process of Islamic Study in universities to achieve the specified goals maximally. The discussion is supported by related literature, expert opinions, and results of previous research relevant to the current study in term of context and issue